THE ESSENCE OF USING PEDAGOGICAL AND PSYCHOLOGICAL TECHNOLOGIES IN EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article discusses the essence of educational technology, its specific aspects and related tasks, the importance of psychological mastery in educational technology.